Al-Ghazali’s Conception of Dreams: The Mechanism of Dreams and the Soul’s Role in Epistemological Knowledge (West Science Interdisciplinary Studies, 2025)
This paper explores Al-Ghazali’s conception of the soul and its role in the mechanism of dreams. According to Al-Ghazali, the soul is an intricate, metaphysical entity composed of interconnected elements—nafs (soul), ‘aql (intellect), qalb (heart), and ruḥ (spirit)—that together shape human behavior and spiritual experiences. Al-Ghazali’s view posits that dreams are not merely psychological or physiological events but metaphysical occurrences influenced by the soul’s capacity to perceive divine knowledge. He argues that the purification of the soul, particularly the heart, is essential for accessing higher truths, with dreams serving as a medium for divine revelation. This metaphysical perspective marks a significant departure from earlier rationalist interpretations, highlighting the spiritual and intuitive aspects of knowledge. Al-Ghazali’s framework of the soul’s role in dreams contributes to the broader Islamic philosophical discourse on the acquisition of knowledge and spiritual development, bridging rationalist thought with mystical traditions.